Thermodynamics and Kinetics of pH-dependent Dissolution of Sparingly Soluble Alkaline Earth Hydroxides in Source-Separated Human Urine Collected in Decentralised Sanitation Systems - Simha, Prithvi; Deb, Chinmoy Kanti; Randall, Dyllon G.; Vinnerås, Björn (Frontiers in Environmental Science, 2022)
Alkaline earth hydroxides are widely used in water and wastewater treatment. Within the emerging niche of source-separating sanitation, these chemicals have found a new application — to prevent urease-catalysed degradation of urea present in freshly excreted human urine. However, little is known about the dissolution behaviour of these hydroxides in biological fluids like human urine. Herein, we investigate the solubility of Mg(OH)2 and examine factors that govern its dissolution in different types of urine (real fresh urine, synthetic fresh urine, synthetic dephosphatised fresh urine and real fresh urine concentrated by CO2-free drying). We report experimentally determined as well as thermodynamically simulated data on Mg(OH)2 solubility, dissolution kinetics, and chemical speciation in urine. We find that it takes between 6 and 16 min for Mg(OH)2 to dissolve and the average solubility in real fresh urine at 25 °C to be 650 mg L-1. We show that solubility is influenced mainly by concentration of organic compounds, soluble phosphate, and magnesium excreted in fresh urine. When fresh urine is supersaturated with Mg(OH)2, the pH increases to >10.5 and urease-catalysed degradation of urea is inhibited for >14 days. Removing 95% water present in urine increase solubility of Mg(OH)2 to 16240 mg L-1 but reduces pH to <10. Because relative increase in Mg(OH)2 solubility decreases as more water is removed and the solubility is retrograde with respect to temperature, to increase the urine pH to >10 and prevent enzymatic ureolysis, the temperature must be kept <29 °C at 75% water removal and <22 °C at 95% water removal. We find this dissolution behaviour of Mg(OH)2 in concentrated urine solutions to be unlike other alkaline earth hydroxides. These findings have significant implications for the design of new sanitation systems that separately collect and recycle plant-essential nutrients present in human urine.